SISTEM INFORMASI FOOD COURT PADA PUSAT PERBELANJAAN SMART SURABAYA - Kurnia, Citra Indah; Tanuwijaya, Haryanto; Sagirani, Tri (Jurnal JSIKA, 2013)
Abstract: In managing a food court generally apply the concept of self-service to the customer, that is order and pay over the counter or cashier. For booth renters, income calculations performed every day manually when the food court closed. It takes a long time and caused frequent occurrence of miscalculation that led to losses and a decrease in turnover for managers and tenants outlets. Facing these problems, food court manager making design and implementation an information systems of the food court at the shopping center smart Surabaya. The food court will apply the touch-screen technology and a smart card in the application to facilitate buyer transactions. For a rent system, food court manager will apply the accounting system every day. Tenants pay rent in accordance with the revenue received each day. With the application of information systems food court at a shopping mall Smart Surabaya has to be used in accordance with management´s desire food court manager. The use of touch screen technology and a smart card has been successful in an application. Besides the need for management information and reporting food court have been met. Key words: Smart Card, Food Court, Touch Screen, Rent.